Tracking and removing Br during the on-surface synthesis of a graphene nanoribbon - Bronner, Christopher; Björk, Jonas; Tegeder, Petra (The journal of physical chemistry. C, Energy, materials, and catalysis, 2015)
The fabrication of graphene nanoribbons (GNRs) requires a high degree of precision due to the sensitivity of the electronic structure on the edge shape. Using Br-substituted molecular precursors, this atomic precision can be achieved in a thermally induced two-step reaction following Br dissociation on a Au(111) surface. Using DFT, we find evidence that the Br atoms are bound to the intermediate polyanthrylene chains. We employ temperature-programmed desorption to demonstrate the associative desorption of HBr and molecular hydrogen during the final cyclodehydrogenation step of the reaction. Both processes are found to have similar activation barriers. Furthermore, we are able to remove Br atoms from the polyanthrylene chains by providing molecular hydrogen. The subsequent formation of GNR via a cyclodehydrogenation demonstrates that Br does not influence this part of the overall reaction.